The role of textbooks in Finnish upper secondary school mathematics: theory, examples and exercises - Viholainen, Antti; Partanen, Miia; Piiroinen, Jani; Asikainen, Mervi A.; Hirvonen, Pekka E. (NOMAD Nordic Studies in Mathematics Education, 2015)
Textbooks are written mainly for students, but they can also be seen as mediators between the intended curriculum and teachers’ practices. The focus of the present study is on how students and teachers at Finnish upper secondary schools perceive and describe their use of the theory, examples, and exercises presented in their mathematics textbooks. Seventy-one students participated in a short survey, and six of them and three of their teachers were interviewed. The results indicate that the theory, examples, and exercises presented in their textbooks have a strong influence on teachers’ work, but for the students the textbooks primarily represent a source of exercises.